2019
DOI: 10.1182/bloodadvances.2019000975
|View full text |Cite
|
Sign up to set email alerts
|

American Society of Hematology 2019 guidelines for management of venous thromboembolism: prevention of venous thromboembolism in surgical hospitalized patients

Abstract: Background:Venous thromboembolism (VTE) is a common source of perioperative morbidity and mortality.Objective:These evidence-based guidelines from the American Society of Hematology (ASH) intend to support decision making about preventing VTE in patients undergoing surgery.Methods:ASH formed a multidisciplinary guideline panel balanced to minimize bias from conflicts of interest. The McMaster University GRADE Centre supported the guideline-development process, including performing systematic reviews. The Gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
341
1
21

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 366 publications
(412 citation statements)
references
References 365 publications
(685 reference statements)
2
341
1
21
Order By: Relevance
“…Results of these trials have informed guideline panels to recommend extended duration prophylaxis (up to 28-35 days) after major orthopedic surgery. 5,11,12 Recent studies have suggested that overall rates of VTE after major orthopedic surgery are falling. A study from a national database from England and Wales of 10-year trends (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014) in medical complications in 540 623 patients undergoing THA found that despite a population with increasing levels of comorbidity, the 90-day mortality rate decreased from 0.60% to 0.15%, the 30-day DVT rate decreased from 1.15% to 0.28%, and the 30-day PE rate decreased from 0.77% to 0.40%.…”
Section: Epidemiology and Trends Over Time In Vte Occurrence After mentioning
confidence: 99%
“…Results of these trials have informed guideline panels to recommend extended duration prophylaxis (up to 28-35 days) after major orthopedic surgery. 5,11,12 Recent studies have suggested that overall rates of VTE after major orthopedic surgery are falling. A study from a national database from England and Wales of 10-year trends (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014) in medical complications in 540 623 patients undergoing THA found that despite a population with increasing levels of comorbidity, the 90-day mortality rate decreased from 0.60% to 0.15%, the 30-day DVT rate decreased from 1.15% to 0.28%, and the 30-day PE rate decreased from 0.77% to 0.40%.…”
Section: Epidemiology and Trends Over Time In Vte Occurrence After mentioning
confidence: 99%
“…In some clinical circumstances, DOACs are used in VTE prophylaxis in patients without cancer . Studies specific to VTE prevention in patients with cancer were warranted, given the benefits observed with LMWH for the prevention of CAT in ambulatory patients receiving systemic anticancer therapy in the SAVE‐ONCO (Evaluation of AVE5026 in the Prevention of VTE in Cancer Patients Undergoing Chemotherapy) and PROTECHT (PROphylaxis of ThromboEmbolism during CHemoTherapy) trials .…”
Section: Evidence Base For the Use Of Rivaroxaban In Catmentioning
confidence: 99%
“…48,49 Still, none of these drugs were approved for use in proximal femur and hip fractures. 4,7,50 Despite the approval of the use of DAOAs in major orthopedic surgeries, current data refer only to rivaroxaban for VTE prophylaxis in surgeries below the level of the knee. In a randomized study with 3,604 patients treated with 40 mg of subcutaneous enoxaparin or 10 mg of oral rivaroxaban, both administered once a day, rivaroxaban was more effective in preventing VTE than enoxaparin (RR: 0.25; 95%CI: 0.09 to 0.75), with no increased risk of bleeding.…”
Section: Pharmacological Thromboprophylaxismentioning
confidence: 99%
“…3 Most data on VTE prevention in orthopedics relates to major orthopedic surgeries, such as knee and hip arthroplasties. [4][5][6] The main guidelines on the subject refer to objective recommendations for surgical prophylaxis, 1,4,7 including clear definitions on the type of drug and the duration of the treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation